The Influence of "Check The Risk of Contracting Coronavirus" Application Quality from Alodokter on The Benefits Gained by Users, to get COVID-19 Early Detection. (November 2020) - Firizkiansah, A; Kriswantara, B; Riana, D; Widayanto, A; Akbar, F; Budi, E S
Abstract: This research uses the IS Success Model DeLone and McLean approach to finding the relationship that occurs between the quality of the Alodokter application to check the risk of contracting coronavirus. This research also tries to figure out how much benefit users have gained in conducting early detection of COVID-19. This Model uses six interrelated variables, including system quality, information quality, service quality, usage, user satisfaction, and clean benefits. With 200 respondents, data analysis uses the partial least square structural equation model (PLS-SEM) method with SmartPLS 3.0 software. This research gives the results that the better the quality of information and services of the Alodokter application, the more benefits gained by the user. However, the system quality factor from the Alodokter application does not affect how much benefits a user gains while they use the app.